BIOTRANSFORMATION OF PENTAGAMAVUNON-0 (PGV-O) : IN VITRO AND IN VIVO STUDIES - ., Sugiyanto; ., Oetari; Nugroho, Agung Endro (Indonesian Journal of Pharmacy, 2003)
Pentagamavunon-0 (PGV-0) or 2,5-bis-(4-hydroxy-3-methoxy benzyilidin) cyclopentanon is a synthetic compound which has been proved to have an anti-inflamatory effect by animal experiments. The study was performed in order to investigate the possible route of biotransformation of PGV-0, which in turn can assist to elucidate the mechanism of its action.The in vivo biotransformation was predicted by identification of all metabolites of PGV-0 presence in urine and faeces after administration orally and intravenously. The in vitro studies were performed using microsomal or sitosolic fraction of the hepar. The metabolites were determined by thin layer chromatography and spectrophotometry.The results indicated that PGV-0 underwent oxydative biotransformation (phase I) and at least produced one metabolite. In vitro studies, PGV-0 also underwent glucuronidation and sulfatation. However, in vivo studies indicated that only metabolites of PGV-0 which have hydroxyl groups underwent conjugation process but PGV-0.Key words: Pentagamavunon-0, biotransformation, in vivo and in vitro.